Pengaruh Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Kesehatan Kota Tegal - Faradisa, Najma El; Wahyuningtyas , Ratri (Jurnal Locus Penelitian dan Pengabdian, 2025)
The decline in performance is thought to be influenced by two main factors, namely the condition of the physical work environment and the level of employee discipline. An uncomfortable or less supportive work environment can have a negative impact on productivity. Likewise, decreased work discipline can hinder the completion of work on time and optimally. These two variables are important concerns because theoretically and empirically they play a role in shaping professional employee work behavior. This study uses a quantitative approach with a survey method through a questionnaire to 104 Tegal City Health Office employees. The analysis technique uses Partial Least Square (PLS) which is considered suitable for analyzing the relationship model between variables with a moderate number of samples. The results of the analysis show that both the physical work environment and work discipline have a positive and significant effect on employee performance. In other words, the better the physical condition of the work environment and the higher the work discipline, the better the performance produced by employees. This finding underlines the importance of creating a comfortable, clean work environment, with good lighting and ventilation, as well as adequate noise and ergonomic management. On the other hand, employee work discipline needs to be continuously improved through the implementation of consistent internal policies, training, and strengthening work ethics and responsibilities. The combination of these two factors has been shown to contribute greatly to increasing employee productivity. As a follow-up, the Tegal City Health Office is advised to adopt a more systematic managerial approach in an effort to improve performance. This can be done through investment in supporting work infrastructure, discipline and time management training, and a periodic evaluation system. The application of technology for work monitoring will also strengthen employee accountability. These efforts are expected to maintain and improve IKU achievements sustainably for optimal public services.